Sistem Monitoring Real-Time pada Pertanian Urban Mandiri Energi Terintegrasi Internet of Things (IoT) - Fath, Yusril Al; Pahlevi, Reza Akbar; Abdillah, Ahmad Muhaimin; Karim, Moh. Hafidhuddin; Diantoro, Markus; Nasikhudin; Ariptiharta (Universitas Andalas, 2025)
Increased evictions of agricultural land have an impact on current agricultural commodity production. Vertical farming/hydroponic systems in urban areas integrated with Photovoltaic (PV) are an alternative solution to two crises, i.e. land constraints and the concept of green energy. The research carried out aims to create a tool for monitoring environmental parameters in an Urban Farming Energy-Independent system that is integrated with the Internet of Things (IoT). The research began with (i) designing the electronic component board and interface of the Human Machine Interface (HMI) system, (ii) assembling and installing devices on hydroponics, (iii) calibration processes as well as device testing, and (iv) integration process with IoT. The monitoring device can run in two modes: manual or automatic. Parameters that can be monitored are water pH, water TDS, water height in the tank, temperature, and humidity. The data entered on the device can also be monitored through the grafana platform. The accuracy of sensor readings on the device reaches over 98%.